Evaluasi Kondisi Perkerasan Metode dan Prediksi Nilai Sisa pada Jalan Hertasning – Jalan Yasin Limpo Kota Makassar - Andi Irvan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study uses primary data in the form of types of damage identified through direct surveys in the field and the thickness of the existing pavement layer carried out by asphalt test-pit testing. The secondary data obtained from the Makassar City Public Works Agency in the form of road pavement data, LHR 2021-2023, CBR, and deflection data in 2023. The results of the analysis show that the condition of Jalan Hertasning - Jalan Yasin Limpo with the pavement on the section is classified as fair with the highest PCI value of 77 in the excellent rating and the lowest of 22 in the very poor rating. The analysis of the new pavement was carried out using the 2017 Bina Marga method, the thickness of the AC-WC layer is 4 cm, AC-BC is 6 cm thick, AC-Base is 8 cm thick, Class A Foundation Layer is 30 cm thick, and Class S additional Foundation Layer is 20 cm thick. Through the mechanistic-empirical method of the KENPAVE program, it shows that the additional pavement layer (overlay) of the Hertasning Street to Yasin Limpo Street section for fatigue cracking damage is 0.0001992 with a load repetition value of 1,441,176 ESAL. The remaining value of the 20-year design life, obtained the thickness of the AC-WC pavement layer of 4 cm, the AC-BC layer of 6 cm, the AC-Base layer of 8 cm, and for the Class A upper foundation layer of 30 cm and an additional layer with Class S aggregate of 20 cm thick which is placed under the Class A Foundation Layer. Meanwhile, based on the KENPAVE program, it shows that during the 20-year design life, the pavement can withstand the load without damage because the load repetition control value is greater than the planned LHR value (Nr). The remaining design life value on Jalan Hertasning to Jalan Yasin Limpo using the Bina Marga 2017 method shows that the planned thickness of the new pavement layer is given an additional layer because the soil bearing capacity is less than 6% so that it is necessary to provide embankment material as a form of soil improvement for the minimum road foundation design in Bina Marga 2017.